CLINICAL AND ECONOMIC JUSTIFICATION OF SOFTWARE SCREENING PERFORMANCE OF COLORECTAL CANCER AT THE REGION LEVEL - Yu. Yu. Petukhova; E. V. Eliseeva; A. G. Petukhova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the study is to assess the clinical and economic effectiveness of the practical implementation results of programmed screening for colorectal cancer (CRC) in the Primorsky Territory using clinical and economic research methods.Materials and methods. In the study, the following kinds of data were used: the statistical data from the regional clinic's cancer registry on the structure of the morbidity and average life expectancy of CRC patients in the Primorsky Territory; the data on the cost of screening studies and the stages of anticancer therapy in accordance with the "Territorial Tariff Agreement on Payment for Medical Care (Medical Services) in the System of Compulsory Health Insurance in the Territory of Primorsky Krai", 2021. Two methods of clinical and economic analysis with the corresponding calculation formulas have been applied. The cost of medical interventions were estimated in accordance with the screening standards and clinical guidelines for the treatment of malignant neoplasms of the colon and rectum, approved by the Scientific and Practical Council of the Ministry of Health of the Russian Federation, 2020.Results. The evidence-based substantiation of screening clinical effects has been obtained: the structure redistribution of colorectal cancer incidence towards the prevalence of early forms by 16.81%; the average increase in the life expectancy of patients with the studied disease is 12.8 months. A natural consequence of these events is the predicted decrease in the mortality rate from CRC in the territory of the subject in the subsequent years. The economic justification of CRC screening software which guarantees a significant saving in health care resources amounting to 23% compared to an alternative strategy, has been demonstrated. It can influence the management decisions on the further strategy of the mass introduction of this medical technology.Conclusion. Currently, CRC screening is the most effective way to reduce morbidity and mortality from this disease. The predominance of the early diagnosis of the disease is extrapolated to significant savings in public health care. A promising direction for further research in the field of CRC screening is the study of its long-term effects, in particular, a detailed clinical and economic analysis of the diagnostics effectiveness and the elimination of premalignant neoplasms.